Comparison of American and Russian Colonization in Two Japanese Animation Film Isao Takahata's Hotaru no Haka and Shigemichi Sugita's Jopanni no Shima - Priventa, Hendrike; Handayani, Umi; Riani, Rosalina Wahyu (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2023)
Animated films are part of literary works with a form of postmodern fiction. It is shown that animated films fulfill the requirements as literary works, which are fictitious, medium in language, and aesthetic. As a literary work, animated films have similar structures, such as characters, characterizations, settings, and plot. The purpose of this study is to compare the traces of American and Russian colonialism in both animated films by looking at their elements such as hybridity and mimicry. The research method that will be used in this research is descriptive qualitative. Descriptive research is research that aims to provide (describe) a condition or phenomenon that exists as it is. The shift in the meaning of "war" is shown from the transformation of the first film to the second film. The thing that needs to be raised is that the second film wants to restore the spirit of Japanese society. The identity of the Japanese people who easily rise from adversity is explored again. Another thing is a form of diplomacy with the Russian state. This is considering that Japan and Russia are two countries side by side. The film Jopanni no Shima wants to be a medium for the relationship between the two countries.